2013
DOI: 10.3233/jvr-130638
|View full text |Cite
|
Sign up to set email alerts
|

Functional limitations in TBI and their relationship to job maintenance following work re-entry

Abstract: Using data from the Job Accommodation Network Information System (JANIS), the utility of self-reported functional limitations was examined in relationship to job maintenance for individuals with traumatic brain injury (TBI) who had returned to work. It was found that memory loss and attention/concentration concerns were the most common functional limitations reported. To further establish which limitations were associated with job maintenance, a binary logistic regression was applied. Results suggested that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Research on TBI and employment is full of examples of emotional dysregulation, behavioral problems and lack of awareness of one´s deficits being particularly disabling in relation to achieving and maintaining gainful employment. 37,38 These factors have also been perceived as barriers to relationships, in particularly intimate, after TBI. 38 Especially mood swings, irritability states and unpredictable patterns of behaviour have been shown to impose the greatest strain on personal relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on TBI and employment is full of examples of emotional dysregulation, behavioral problems and lack of awareness of one´s deficits being particularly disabling in relation to achieving and maintaining gainful employment. 37,38 These factors have also been perceived as barriers to relationships, in particularly intimate, after TBI. 38 Especially mood swings, irritability states and unpredictable patterns of behaviour have been shown to impose the greatest strain on personal relationships.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of a variety of cognitive, behavioural and emotional disorders; impaired psychosocial, physical and sensory functioning; and medical symptoms, individuals who sustain TBI often experience difficulty becoming competitively employed post injury and maintaining employment for extended period of time. 37,43,45 Essential elements in the holistic neurorehabilitation programmes are individually tailored placements and supported work trials which help patients to find productive activities that fit their abilities and interests after TBI. 7,11,13,46 The effort to accomplish consistence between the capabilities of the patients and the requisites of the work or other productive activities seems to be crucial.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent problems reported were remembering (96%) and concentrating (91%). Similarly, in the United States of America (USA), Artman and McMahon (2013) researched the self-reported functional limitations of 160 individuals following traumatic brain injury in relation to job maintenance following return to work, and found memory loss, attention, concentration and behavioural difficulties most reported. Despite Artman and McMahon (2013) relying on the self-report of participants who may have lacked self-awareness, their findings were consistent with Benedictus et al (2010) in the Netherlands.…”
Section: Background Literature Reviewmentioning
confidence: 99%
“…Similarly, in the United States of America (USA), Artman and McMahon (2013) researched the self-reported functional limitations of 160 individuals following traumatic brain injury in relation to job maintenance following return to work, and found memory loss, attention, concentration and behavioural difficulties most reported. Despite Artman and McMahon (2013) relying on the self-report of participants who may have lacked self-awareness, their findings were consistent with Benedictus et al (2010) in the Netherlands. Benedictus et al (2010), on evaluating cognitive and behavioural disturbances related to return to work for 434 individuals following traumatic brain injury, found that participants encountered problems with cognitive (62%), behavioural (55%) and social (49%) difficulties.…”
Section: Background Literature Reviewmentioning
confidence: 99%
“…Employment rates for persons with disabilities were higher for individuals who were male, White, married, or had higher levels of educational attainment (Sevak, Houtenville, Brucker, & O’Neill, 2014). The type of disability can influence employment outcomes, with variations seen in employment for persons with limitations that were sensory (Appelman et al, 2012; Darensbourg, 2013; Giesen & Cavenaugh, 2013; Houston, Lammers, & Svorny, 2010; Kelly, 2013; McDonnall, Li, & Crudden, 2013) and functional (Andelic, Stevens, Sigurdardottir, Arango-Lasprilla, & Roe, 2012; Arango-Lasprilla et al, 2009; Artman & McMahon, 2013; Baune et al, 2010; Giugiario et al, 2012; Jones & Crews, 2013; J. S. Krause, 2010; I.…”
Section: Literature Reviewmentioning
confidence: 99%